PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA WISATA ALAM SUMBER MARON KARANGSUKO, PAGELARAN, MALANG) - Karina Putri Melati; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study aims to discuss and analyze experiential marketing towards customer satisfaction. The population consists of 500 and the sample consists of 83 consumers. Data collection in this study through a questionnaire. Data analysis in the study using SPSS version 14. Testing the application of data used in this study include multiple regression analysis, validity test, reliability test, normality test, classic assumption test, and research hypothesis test.               Indicator analysis shows that the marketing experience of taste indicators, thinking, acting, and partial relations have a partial interest in customer satisfaction while indicators feel no significant effect on customer satisfaction. Experience based marketing strategies that consist of indicators of feeling, feeling, thinking, acting and relating to influencing consumers.Keywords: sense, feel, think, act, and relate